Known and Potential Invertebrate Vectors of Raspberry Viruses - Tan, Jiunn Luh; Trandem, Nina; Fránová, Jana; Hamborg, Zhibo; Blystad, Dag-Ragnar; Zemek, Rostislav (Viruses, 2022)
The estimated global production of raspberry from year 2016 to 2020 averaged 846,515 tons. The most common cultivated Rubus spp. is European red raspberry (Rubus idaeus L. subsp. idaeus). Often cultivated for its high nutritional value, the red raspberry (Rubus idaeus) is susceptible to multiple viruses that lead to yield loss. These viruses are transmitted through different mechanisms, of which one is invertebrate vectors. Aphids and nematodes are known to be vectors of specific raspberry viruses. However, there are still other potential raspberry virus vectors that are not well-studied. This review aimed to provide an overview of studies related to this topic. All the known invertebrates feeding on raspberry were summarized. Eight species of aphids and seven species of plant-parasitic nematodes were the only proven raspberry virus vectors. In addition, the eriophyid mite, Phyllocoptes gracilis, has been suggested as the natural vector of raspberry leaf blotch virus based on the current available evidence. Interactions between vector and non-vector herbivore may promote the spread of raspberry viruses. As a conclusion, there are still multiple aspects of this topic that require further studies to get a better understanding of the interactions among the viral pathogens, invertebrate vectors, and non-vectors in the raspberry agroecosystem. Eventually, this will assist in development of better pest management strategies.
Keywords: Animals; Viruses; mšice; Nematoda; soft fruit; aphids; Aphids; viry; virus transmission; Rubus; integrated pest management; virus control; virus-vector interactions; hlístice; arthropod pests; mites; nematodes; zvířata; Rubus idaeus